A Case Study On The Processor Based Signalling System Used In Double Track Projects For Keretapi Tanah Melayu Berhad (KTMB) - Satiaselan, Venuka (2009)
In this paper, a study is conducted to understand and further to examine the effectiveness of the existing processor based signalling system along with the duplication system as a fail safe route interlocking system used in double track projects for Keretapi Tanah Berhad (KTMB)